Practical PHP and MySQL : building eight dynamic web applications - Bacon, Jono (Upper Saddle River, New Jersey : Prentice-Hall, 2007)
Helps you build dynamic web sites fast, with PHP and MySQL. This book includes eight ready-to-run, real-world applications - backed by diagrams and screenshots, well-documented code, and practical explanations. It shows you how to connect with databases, upload content, perform cascading deletes, edit records, validate registrations, and more
Chapter 1 A New Approach -- Chapter 2 Getting Started with PHP and MySQL -- Chapter 3 Running the Projects -- Chapter 4 Building a Weblog -- Chapter 5 Discussion Forums -- Chapter 6 Creating a Shopping Cart -- Chapter 7 Building an Online Auction Site -- Chapter 8 Creating a Web-Based Calendar -- Chapter 9 FAQ Content Management System 3-- Chapter 10 Building a Re-Usable Project -- Chapter 11 Building a News Web Site
Includes index.
Keywords: MYSQL (ELECTRONIC RESOURCE)